2019
DOI: 10.1039/c9cp01883b
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian machine learning for quantum molecular dynamics

Abstract: This article discusses applications of Bayesian machine learning for quantum molecular dynamics.One particular formulation of quantum dynamics advocated here is in the form of a machine learning simulator of the Schrödinger equation. If combined with the Bayesian statistics, such a simulator allows one to obtain not only the quantum predictions but also the error bars of the dynamical results associated with uncertainties of inputs (such as the potential energy surface or

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
136
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(139 citation statements)
references
References 100 publications
(180 reference statements)
0
136
0
Order By: Relevance
“…Many different techniques have been developed for fitting multi-dimensional PES (for representative examples, see Refs. [1][2][3][4][5][6]). A major thrust of recent research has been to develop approaches for fitting PES of polyatomic systems by machine learning (ML) models .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many different techniques have been developed for fitting multi-dimensional PES (for representative examples, see Refs. [1][2][3][4][5][6]). A major thrust of recent research has been to develop approaches for fitting PES of polyatomic systems by machine learning (ML) models .…”
Section: Introductionmentioning
confidence: 99%
“…Using GPs to construct PES for polyatomic systems has several advantages over other methods [6]. First, it has been shown that accurate GP models can be obtained with a much smaller number of potential energy points than required for any other fitting method [21,24].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, in chemical physics, as recently shown, datadriven approaches bring a new perspective to solve some of the most delicate problems of the field. [13][14][15][16] In this paper, we present a data-driven approach to dipole moments of diatomic molecules and its relationship with spectroscopic constants. We show that, after compiling the most exhaustive list of dipole moments for diatomics up to date (to the best of our knowledge) into a dataset, it is possible to learn the dipole moment of diatomic molecules based upon atomic and molecular properties with a relative error t5%.…”
Section: Introductionmentioning
confidence: 99%
“…A substantial amount of materials data are accumulated in public databases [1][2][3], and machine-learning-based design of materials is increasingly common in recent years [4][5][6]. The problem of materials design is mathematically formulated as a black-box optimization problem, where a large number of candidates are available and the goal is to find the candidate with best target property via a minimum number of observations.…”
Section: Introductionmentioning
confidence: 99%